In the shadow of the Civil War: Greek students at VGIK, 1950s–1970s. (4th May 2019) - Katsakioris, Constantin
ABSTRACT: Part of a special issue devoted to the centenary of the Film Institute VGIK, this article considers a forgotten page of the history of the film school as the alma mater of the celebrated writer Alki Zei, the award-winning filmmakers Fotos Lambrinos and Christos Siopahas and other important Greek cultural figures. Along with the studio Mosfilm, VGIK was both a unique school and a safe haven for Greek refugees and leftist students, who found themselves in the Soviet Union in the period between the end of the Greek Civil War (1946–1949) and the fall of the dictatorship in 1974. This article revisits the history of the Greek friends of Andrei Tarkovsky, and of the students of Mikhail Romm and Iurii Egorov. These Greek students at VGIK had experienced repression, authoritarianism and exile; they were marked by the division of Cyprus and haunted by the defeat in the Civil War. To these painful experiences and dramatic events, they responded with their art.